(3TeS GdYdhe hOhGA cdGe GdYQH ef Gdcdhes - (3fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdbOje CeG HYO ,aEf CaVd GddZGJ eG fRd Hg GdbQBf GdeLjO hdG SHjd Edi eYQaJg hYdeg EdG HeYQaI Yde gPg GddZI GdYQHjI hcPdc GdMOjK Yf GdQShd Udi Gddg Ydjg hSde dG jYQa EdG HeYQaI s
(3BNQgG (B:s
(3ef cJGH GdWGA , HGH GdWGA , heG HYOgeG ef GdMQha ai GdeVGYa hGdWH GdWHjH , hjbGd aMd WH EP cGf MGPbG HGdVQGH hHYjQ WH GdVhGFf LeY VGFfI , hgj GdTGI ef GdZfe , NdGa GdeYfi s
(3GdfSNI HgG MhGTs
(3HMhGSjgG JYdjbGJ hTQhNs
(3HgG fXGe GdJYbjHIs
(3HChQGbgG GdChdi JbWjY s
(3fSNI NGeSI s
(3hbO aQZ GdeDda ef JCdjaI ai TghQ QeVGf SfI (B570(3g` s
Keywords: (3GddZIs